PENGGUNAAN MEDIA PAPAN FLANEL UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN KEMAMPUAN MENGENAL KATA - Erni Patul Aini (DIADIK, 2023)
This study aims to 1) analyze the use of flannel board media in increasing learning motivation for group B children at Al Wakhidah Kindergarten Pasar Bembah North Bengkulu 2) analyze the use of flannel board media in improving word recognition skills for group B children in Al Wakhidah Kindergarten Pasar Bembah Bengkulu Utara 3) analyzed the effectiveness of using flannel board media in improving the ability to recognize words for children in group B at Al Wakhidah Kindergarten, Pasar Bembah, North Bengkulu compared to the media that had been used by teachers. This research uses Classroom Action Research (CAR). Classroom Action Research is a translation of Classroom Action Research, which is an Action Research conducted in class. The population in this study were students of TK Al Wakhidah Pasar Bembah, North Bengkulu, totaling 30 people divided into 3 classes. The population in this study is also the sample or research subject. The sample in this study was for the CAR class that would be treated with the play method, group B.1 consisted of 10 children. While B.2 as many as 10 children as an experimental class and B.3 as a control class with a total of 10 children from Al Wakhidah Kindergarten, Pasar Bembah, North Bengkulu. The results of the study revealed that 1) the use of flannel board media was able to increase children's motivation. 2) The application of flannel board media can improve children's ability to recognize letters. Children are motivated to recognize letter by letter. 3) This research proves that the application of flannel board media will be more effective than the conventional method. The results of the study in the experimental class and control class showed that there was a significant increase in the ability to recognize letters in children after using flannel board media in learning.